"It may be legal, but it is not treated equally": marriage equality and well-being implications for same-sex couples. Issue 1 (2nd January 2020) - Kennedy, Heather R.; Dalla, Rochelle L.
Abstract: Despite the monumental victory of marriage equality for same-sex couples, sexual and gender minorities continue to face barriers toward full equality in a variety of contexts. This study adds to limited research examining the impact of marital recognition on personal and relational well-being. Using a mixed-methods approach we explored the experiences of 218 Midwestern, married, same-sex couple members. We contend perceptions of recognition influence distinct aspects of personal well-being for those in married same-sex relationships. Individuals residing in states without marriage equality displayed significantly greater negative affect than their peers in marriage equality contexts. Qualitative findings revealed themes of legitimacy and security following marriage, but clear distinctions in experiences were evident based on legal recognition. Collectively, participants' expressed a stronger relational bond following marriage. Perceived recognition, via state policy, served as a catalyst for many couples to take refuge in specific residential locales. Yet, regardless of context, narratives depicted minority stress experiences including encountering affirmation and opposition to their identities and relationships.